Controvérsias acerca da lei das inelegibilidades a partir da lei complementar 135/2010 - Melo, Rafael Veras Castro (2013)
This work consists of the analysis relating to the discussion of the assumptions of inelegibility, emphasizing the dubious and controversial issues regarding the application of this institute after the publication of Supplementary Law 135/2010, Clean Record Law. Preliminarily, it emphasizes the jurisprudential evolution that led to legal changes occurred as well as the relationship between these and the clamor of society by greater preservation of the values of probity and morality in Brazilian Election Law. After that, general concepts are clarified to ineligibility, discussing its features and its regulation by the various existing laws, such as the Supplementary Law 64/90. In the next chapter, we question the divergent positions associated to the various implications of the use of legislation, highlighting the solution found by the Courts to the doubts and possible criticism. Then covers up the prescription penal institutes and their effects on harvest election of replacement candidates and their relationship with the democratic principle, the new ineligibility due to ethical and professional violations, among other innovations. Finally, we discuss the established jurisprudence of the Supreme Electoral Tribunal on the issues and try to find ways for the future in these matters.